2012
DOI: 10.1186/1477-5956-10-23
|View full text |Cite
|
Sign up to set email alerts
|

A comparative proteomic study identified LRPPRC and MCM7 as putative actors in imatinib mesylate cross-resistance in Lucena cell line

Abstract: BackgroundAlthough chronic myeloid leukemia (CML) treatment has improved since the introduction of imatinib mesylate (IM), cases of resistance have been reported. This resistance has been associated with the emergence of multidrug resistance (MDR) phenotype, as a BCR-ABL independent mechanism. The classic pathway studied in MDR promotion is ATP-binding cassette (ABC) family transporters expression, but other mechanisms that drive drug resistance are largely unknown. To better understand IM therapy relapse due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 83 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…[31]. In addition to being resistant to daunorubicin and Imatinib [35], MDR cells were shown to express more BCR-ABL kinase and MDR1 than K562 [48], presenting a broad pattern of resistance that includes BCR-ABL independent resistance mechanisms.…”
Section: Resultsmentioning
confidence: 98%
“…[31]. In addition to being resistant to daunorubicin and Imatinib [35], MDR cells were shown to express more BCR-ABL kinase and MDR1 than K562 [48], presenting a broad pattern of resistance that includes BCR-ABL independent resistance mechanisms.…”
Section: Resultsmentioning
confidence: 98%
“…This IM dose was previously reported by our group as the IC 50 for K562 cells, corroborating with literature data. 19 We verified reduced apoptosis induction in K562 cells treated with IM after the 5-Aza-dC treatment (Fig. 6A), compared with K562 cells treated with IM alone.…”
Section: Lrpprc Regulates Abcb1 Expression Through the Invmed1 Bindinmentioning
confidence: 85%
“…Subsequently, we performed a comparative proteomic study to identify proteins that are potentially involved in IM/ MDR-cross resistance in CML, and we reported that LeucineRich protein 130 (LRPPRC) is potentially involved in such resistance. 19 LRPPRC is a member of the pentatricopeptide repeat protein family and is described as a multifunctional protein involved in homeostasis, microtubule alterations, RNA stability, DNA/ RNA binding, transcriptional activity in the mitochondria, metabolic processes, RNA nuclear export and, more recently, in tumorigenesis. [20][21][22][23][24][25][26][27][28][29][30][31][32] Nuclear transcription activity was described in acute lymphoblastic leukemia (ALL) in an MDR cell model.…”
Section: Introductionmentioning
confidence: 99%
“…However, and in spite of the drug's established efficacy and generally excellent patient response, primary or acquired resistance is an important clinical issue that frequently leads to a switch of therapy (Apperley, 2007;Karvela et al, 2012;Quintás-Cardama et al, 2009). Resistance mechanisms include several well-characterized processes that implicate the Bcr-Abl kinase, more specifically at the level of point mutations in the kinase domain (Karvela et al, 2012;Quintás-Cardama et al, 2009;Vaidya et al, 2012), but in an estimated 20% of CML cases resistance occurs through Bcr-Abl activity-independent mechanisms (e.g., activation of multidrug resistance pumps), some of which remain uncharacterized (Colavita et al, 2010;Correa et al, 2012;Hentschel et al, 2011;Lee et al, 2007). These mechanisms are of particular relevance in the advanced stages of the disease, when treatment failure is frequently attributed to Bcr-Abl-independent resistance (Eiring et al, 2011;Quintás-Cardama et al, 2009).…”
Section: Introductionmentioning
confidence: 99%